Suppression of free associations in the think/no-think paradigm - Klein, Kimberly, author; Cleary, Anne, advisor; Rhodes, Matt, committee member; Henry, Kim, committee member; Robinson, Dan, committee member (Colorado State University. Libraries, 2014)
Empirical support for forgetting due to memory suppression, the act of intentionally pushing material out of one's mind, has been found using the think/no-think (TNT) paradigm. However, there is little consistency in results across experiments using this paradigm, with no known systematic difference that can predict whether a given experiment will be successful or not. Prior published findings and pilot data suggest that one mediating factor may be speed of response, with fast responders demonstrating suppression while slow responders do not. In order to directly investigate this hypothesis, the present with-in subjects experiment manipulated time allowed for subjects to respond in a free-association variation of the standard TNT paradigm. Results did not show any differences based on speed of response, or on other qualitative information provided by participants. It remains unclear whether there is a particular factor that can predict the success of the TNT paradigm.
Keywords: suppression; memory suppression; think/no-think; inhibition; memory